Digital Bookkeeping Training Using Applications for Business Micro, Small and Medium Enterprises (SME) Tellu Silo Aldian Jaya - Nurina Saffanah; Rahayu Alkam (Manunggal Halim Jaya, 2022)
Tellu Silo Aldian Jaya to start its business in 2019 as a micro business engaged in processing local food sources into packaged food and beverage products. The first products produced were a drink made from red ginger, coffee and lemon grass named Jahe's Kopi and a drink made from milk and ginger named Jahe's Susu. The rapid development of Tello Silo Aldian Jaya SMEs is in line with the prospects for SMEs in Indonesia which continue to increase every year. This community partnership program is directed at helping good financial management so that it has a positive impact on the business continuity of the Tellu Silo MSME business. The benefits that are expected to be obtained by partners after participating in this service program are that the target community has an understanding regarding the urgency and basic concepts of bookkeeping and accounting. Digital bookkeeping by utilizing the La Mikro application is an output product of this program which is expected to be able to overcome the problem of the lack of competent human resources in the fields of finance and accounting at Tellu Silo Aldian Jaya.